Odpowiedź :
Odpowiedź:
w(x) = (x² + 3x + 6)(x - 2)
Szczegółowe wyjaśnienie:
w(x) = x³ + x² - 12
w(x) = x³ -2x² + 3x² - 6x + 6x - 12
w(x) = x²(x -2) + 3x(x - 2) + 6(x - 2)
w(x) = (x² + 3x + 6)(x - 2)
x² + 3x + 6
Δ = 3² - 4 · 1 · 6
Δ = 9 - 24
Δ = - 15 < 0
brak miejsc zerowych
zatem ostatecznie w(x) = (x² + 3x + 6)(x - 2)
Odpowiedź:
w(x ) = x³ + x² - 12
x = 2 bo 2³ +2² - 12 = 8 + 4 - 12 = 0
( x³ + x² - 12) : ( x - 2 ) = x² + 3 x + 6
- x³ +2 x²
--------------
3 x² - 12
- 3 x² + 6 x
---------------
6 x - 12
- 6 x + 12
---------------
0
Szczegółowe wyjaśnienie:
x² +3 x + 6 = 0 Δ = 9 - 4*1*6 < 0 Brak rozwiązań
Odp. x = 2
============
x³ + x² - 12 = ( x - 2)*( x² +3 x + 6)
==============================